Evaluation of bone length and number of osteotomies utilizing the osteocutaneous radial forearm free flap for mandible reconstruction: An 8‐year review of complications and flap survival. Issue 3 (26th May 2015) - Silverman, Dustin A.; Przylecki, Wojciech H.; Arganbright, Jill M.; Shnayder, Yelizaveta; Kakarala, Kiran; Nazir, Niaman; Tsue, Terance T.; Girod, Douglas A.; Andrews, Brian T.
Abstract: Background: The purpose of this study was to assess the impact of bone harvest length and multiple osteotomies on osteocutaneous radial forearm free flap (RFFF) complication rates. Methods: A retrospective chart review was conducted for patients undergoing osteocutaneous RFFF reconstruction during an 8‐year period. Results: One hundred fifty‐five osteocutaneous RFFF procedures were performed. Recipient‐site flap complications were 18 of 55 (32.7%) when bone harvest length was less than 7 cm and 40 of 100 (40.0%) when it was ≥7 cm. No osteotomies were performed in 69 of 155 cases with a corresponding complication rate of 30.4% (21 of 69). One osteotomy was utilized in 69 of 155 flaps, whereas 17 of 155 required more than 1 osteotomy; complications were experienced in 42% (29 of 69) and 47% (8 of 17) of these cases, respectively. Conclusion: Osteocutaneous RFFF complication rates were only slightly higher when the bone length was ≥7 cm or when multiple osteotomies were required. © 2015 Wiley Periodicals, Inc. Head Neck 38: 434–438, 2016